Character Education in Shaping a Disciplined and Noble Generation: A Study of Children Aged 4-6 Years at RA Perwanida Brawijaya - Arin, Arini Mubaroroh; Sa'dun Akbar (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This study aims to uncover the implementation of character education for children aged 4-6 years at RA Perwanida Brawijaya, Pamekasan. The method used is a qualitative approach with descriptive data collection, using the principal and teachers of RA Perwanida Brawijaya as primary data sources, and literature from books and the internet as secondary data. The research findings indicate that character education at RA Perwanida Brawijaya, Pamekasan, is implemented through routine activities, incidental activities, and the